MAJOR TRENDS IN AVIATION INDUSTRY DURING COVID-19 - Tikhonov, Alexey; Sazonov, Andrey (Journal of Applied Engineering Science, 2022)
The purpose of the research in this article is to identify the main trends in the development of aviation industry during COVID-19 pandemic. The authors identify the main problems facing aviation industry in the context of the developing world crisis and possible ways to solve them. As a working hypothesis, it is proposed to form the basic concepts necessary for preliminary preparation and implementation of operational measures to restore passenger and cargo aviation. Taking into account the main threats facing the aviation industry during COVID-19, the article proposes the organizational and economic mechanisms to restore the industry. Short-term, medium-term and long-term recovery scenarios are considered, taking into account the relevant factors that have a certain impact. The study is based on a comprehensive analysis of documentary data provided by government agencies in a number of European countries. Openly printed materials from the International Civil Aviation Organization (ICAO) are also used in the analytical report "Consequences of new coronavirus COVID-19 in civil aviation: analysis of economic impact". The research methods are working papers from the European and North Atlantic Offices of ICAO aimed at rebuilding the aviation industry after COVID-19 pandemic. An analysis of global and Russian passenger traffic for Q1-Q4 (quartile) of 2021 and a development forecast for Q1-Q2 of 2022 is provided. The scenario problems facing the aviation industry in the context of COVID-19 crisis are identified. There are key concepts necessary to start preparation and implementation of effective measures to restore the aviation industry.